INFORMATION SAFETY: TOP FIVE FAKE NEWS IN THE ROMANIAN MEDIA (2022) - UNGUR-BREHOI , Carmen (International Journal of Legal and Social Order, 2022)
The phenomenon of “fake news” is increasing in both the online area in Romania and in other media: newspapers, radio and television. The pandemic and the war in Ukraine have been bombarded with such information. Some theorists even speak of a hybrid-information war that precedes the war in Ukraine (see the 2016 USA election and evidence of Russian Federation interference in the process). In Central and Western Europe, the phenomenon is explosive through the falsification of documents, the spread of fake news, trolls, and website cloning. How safe is information for the public? How much are journalists making sure they inform correctly, check information so they can maintain the information safety?